Quantitative analysis of mineral content in enamel using laboratory microtomography and microhardness analysis. - art. no. 631823 - Vieira, A. E. M.; Delbem, Alberto Carlos Botazzo [UNESP]; Sassaki, K. T.; Cannon, M. L.; Stock, S. R. (Spie - Int Soc Optical Engineering, 2006)
This study evaluates laboratory microtomography and microhardness analysis for quantifying the mineral content of bovine enamel. Fifty enamel blocks were submitted individually for 5 days to a pH-cycling model at 37 degrees C and remained in the remineralizing solution for 2 days. The blocks were treated twice daily for 1 min with NaF dentifrices (Placebo, 275, 550, 1,100 mu g F/g and Crest (R)) diluted in deionized water. Surface microhardness changes (%SMH) and mineral loss (Delta Z) were then calculated. Laboratory microtomography was also used to measure total mineral lost (LMM). Pearson's correlation (p < 0.05) was used to determine the relationship between different methods of analysis and dose-response between treatments. Dentifrice fluoride concentration and %SMH and Delta Z were correlated (p < 0.05). There was a positive relationship (p < 0.05) when comparing LMM vs. Delta Z; a negative relationship (p < 0.05) was found for %SMH vs. LMM and %SMH vs. Delta Z. Therefore, both mineral quantification techniques provide adequate precision for studying the bovine enamel-pH-cycling demineralization/remineralization model.
Keywords: enamel; laboratory microtomography; microhardness